Neofusicoccum parvum associated with pomegranate branch canker in Iran. Issue 2 (27th February 2020) - Golmohammadi, Hadi; Arzanlou, Mahdi; Rabbani Nasab, Hojjatollah
Abstract: Pomegranate ( Punica granatum ) is native to Iran and neighbouring countries and is negatively affected by a wide range of diseases. Canker and dieback diseases caused by Cytospora punicae and members of the family Botryosphaeriaceae are the main trunk diseases on pomegranate. In summer 2017, progressive dieback of branches on some young pomegranate trees was observed in orchards of the Gorgan Region (Golestan province, Northeast Iran). Fungal colonies with similar colony colour were isolated from symptomatic tissues. The identity of the causal agent was determined as Neofusicoccum parvum, based on a polyphasic taxonomic approach including morphological features of conidiomata and phylogenetic inference based on the ITS‐rDNA region and translation elongation factor 1 alpha ( tef1‐α ) gene. Koch's postulates were fulfilled using an excised shoot method. This study provides the first report on the occurrence of N. parvum as a cause of branch canker on pomegranate in Iran.